1993
DOI: 10.1002/oms.1210281030
|View full text |Cite
|
Sign up to set email alerts
|

Formation and identification of ionized and neutral cumulenes, RNCCCNH, by tandem mass spectrometry

Abstract: Using a combination of mass spectrometric techniques, it is shown that 5-amino-4-cyanoisoxazole molecular ions (I+'), lose isocyanic acid HNC=O, not fulminic acid, HCGN + 0. Metastable ion fragmentations (unimolecular and collision induced) and deuterium-labelling experiments are in agreement with the formation of a cumulenic structure, HN=C=C=C=NH (3a"). The hitherto unreported molecules HNCCCNH are also shown to be stable when formed in the low-pressure gas phase of the mass spectrometer by using the techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…There are many examples of sensitive compounds (especially carrying O᎐H or N᎐H functions) isomerising extremely readily under FVT conditions to more stable tautomers in reactions formally involving 1,3-H shifts; in reality, these reactions are more likely bimolecular or wall-catalysed. 23 The observation that alkylthiomethyleneketenes such as 9 cyclise to thiophenones 11 (Scheme 3), whereas the oxy analogues 15 do not cyclise to furanones 17, is in good agreement with ab initio calculations of the activation barriers and energies of the zwitterionic intermediates (e.g.…”
Section: Discussionsupporting
confidence: 57%
“…There are many examples of sensitive compounds (especially carrying O᎐H or N᎐H functions) isomerising extremely readily under FVT conditions to more stable tautomers in reactions formally involving 1,3-H shifts; in reality, these reactions are more likely bimolecular or wall-catalysed. 23 The observation that alkylthiomethyleneketenes such as 9 cyclise to thiophenones 11 (Scheme 3), whereas the oxy analogues 15 do not cyclise to furanones 17, is in good agreement with ab initio calculations of the activation barriers and energies of the zwitterionic intermediates (e.g.…”
Section: Discussionsupporting
confidence: 57%
“…Calculations (vide infra) have indeed indicated that a low-lying isomer HNCNSH •+ exists on the CH 2 N 2 S •+ potential energy surface and that rearrangement of NH 2 CNS •+ to HNCNSH •+ has a moderate energy barrier. The intensity of this peak is drastically decreased in the NR mass spectrum (Figure b) probably because of a higher energy deposition in the NR experiment . The very high intensity of the recovery signal at m / z 74 is again indicative of the stability of the neutral sulfide H 2 NC⋮N→S 7 in the gas phase.…”
Section: Resultsmentioning
confidence: 93%
“…2 We are currently extending this fruitful interplay between theory and experiment to the characterization of bisimines RN=C=C=C=NR'.3 Thecalculated CCC bending potential, however, is extremely flat.…”
Section: Resultsmentioning
confidence: 99%